Effects of Lactic Acid Bacteria Fermentation on the Release and Biotransformation of Bound Phenolics in Ma Bamboo Shoots (Dendrocalamus latiflorus Munro) - Liangshi Zhang (Foods, 2025)
Lactic acid bacteria fermentation has the potential to enhance the biological activity of bamboo shoot polyphenols. The aim of this study was to investigate the release pattern and biotransformation mechanism of bound phenols from bamboo shoots prepared by fermentation with Lactobacillus acidophilus, Pediococcus pentosaceus, and Lactobacillus plantarum. The results showed that compared with unfermented controls, bound forms of vanillic acid, p-coumaric acid, and ferulic acid significantly decreased, while their free forms increased substantially after 6 d fermentation (p < 0.05). Quantitative analysis revealed particularly dramatic transformations for p-coumaric acid, which showed a 30–3000% increase in free form, and ferulic acid with a 203–359% increase in free form. Pediococcus pentosaceus demonstrated outstanding performance in bound phenol release and conversion, correlating with its higher β-glucosidase (0.67 U/g) and ferulic acid esterase (0.69 U/g) production. FITR, SEM, and IFM also demonstrated that LAB fermentation led to changes between free and bound phenols in bamboo shoots. These results demonstrate Pediococcus pentosaceus fermentation most effectively liberates bound phenolics, significantly improving their bioavailability for functional food applications.